2006
DOI: 10.2116/analsci.22.1577
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Voltammetry of 2-(5-Bromo-2-pyridyl)azo-5-[N-n-propyl-N-(3-sulfopropyl)amino]phenol on a Carbon Paste Electrode in the Presence of Organic Cations and Polycation

Abstract: The adsorption of ion-association complexes on a carbon paste electrode (CPE) was investigated by cyclic voltammetry using an electroactive hydrophobic anion probe. The redox reactions of 2-(5-bromo-2-pyridyl)azo-5-[N-n-propyl-N-(3-sulfopropyl)amino]phenol (5-Br-PAPS), the analytical probe, were irreversible. The reduction of the azo group and the oxidation of the phenol were observed at -0.1 V and 0.9 V vs. SCE, respectively, in a 0.1 mol L -1 H2SO4 solution. The peak currents for the redox reaction increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…All experimental results described below were obtained using the HTA ion as the indicator ion and the HTA-ISE. According to the colloidal titration of PHMB-HCl by TB indicator at less than pH 2, 34 the result agreed with the total value of non-aqueous titration and argentometric titration. Thus, one mole of the unit concentration of PHMB-HCl quantitatively reacted with two moles of the unit concentration of PVSK.…”
Section: Selection Of the Indicator Ionsupporting
confidence: 75%
See 2 more Smart Citations
“…All experimental results described below were obtained using the HTA ion as the indicator ion and the HTA-ISE. According to the colloidal titration of PHMB-HCl by TB indicator at less than pH 2, 34 the result agreed with the total value of non-aqueous titration and argentometric titration. Thus, one mole of the unit concentration of PHMB-HCl quantitatively reacted with two moles of the unit concentration of PVSK.…”
Section: Selection Of the Indicator Ionsupporting
confidence: 75%
“…So far, many determination methods for polyelectrolytes, such as a poly(diallyldimethylammonium chloride) (Cat-floc), were developed by using conductometry, 1 turbidimetry, 2 potentiometry using ion-selective electrodes (ISEs), [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] colorimetric Toluidine Blue (TB) method, [22][23][24] fluorometry, [25][26][27][28] photometric titration method [29][30][31] and a voltammetric method. [32][33][34] However, only a few determination methods of PHMB-HCl have been reported. Hattori et al 34 have reported an indirect determination of PHMB by using adsorptive voltammetry of 2-(5-bromo-2-pyridyl)azo-5-[N-npropyl-N-(3-sulfopropyl)amino]phenol on a carbon paste electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PHMB-HCl is a polycation, an organic redox anion is useful to the determination of PHMB-HCl using adsorption voltammetry. Here we used 2-[(5-bromo-2-pyridyl)azo]-5-[N-n-propyl-N-(3-sulfopropyl)amino] phenol (5-Br-PAPS) as the analytical probe (Hattori et al 2006). The adsorptive voltammograms of 5-Br-PAPS in 0.01 m H 2 SO 4 solution indicated two waves, reduction of the azo at -0.1 V vs. SCE and oxidation of the phenol at 0.9 V vs. SCE (Figure 9, broken line).…”
Section: Indirect Determination Of Phmb-hcl By Using Adsorptive Voltamentioning
confidence: 99%
“…11-2210, f3 mm, BSA) with TGP-2 carbon powder and bis(2-ethylhexyl)phtalate was used. 10,17 All measurements were performed using freshly prepared electrode surfaces. A platinum wire and a saturated calomel electrode (H type SCE, BAS) or KCl Ag/AgCl electrode (RE-5B, BAS) were used as counter and reference electrodes, respectively.…”
Section: Apparatus and Reagentsmentioning
confidence: 99%